Water-Restrained Hydrogel Electrolytes with Repulsion-Driven Cationic Express Pathways for Durable Zinc-Ion Batteries - Lin, Dewu; Lin, Yushuang; Pan, Ruihong; Li, Jiapei; Zhu, Anquan; Zhang, Tian; Liu, Kai; Feng, Dongyu; Liu, Kunlun; Zhou, Yin; Yang, Chengkai; Hong, Guo; et al. (Nano-Micro Letters, 2025)
The development of flexible zinc-ion batteries (ZIBs) faces a three-way trade-off among the ionic conductivity, Zn2+ mobility, and the electrochemical stability of hydrogel electrolytes. To address this challenge, we designed a cationic hydrogel named PAPTMA to holistically improve the reversibility of ZIBs. The long cationic branch chains in the polymeric matrix construct express pathways for rapid Zn2+ transport through an ionic repulsion mechanism, achieving simultaneously high Zn2+ transference number (0.79) and high ionic conductivity (28.7 mS cm−1). Additionally, the reactivity of water in the PAPTMA hydrogels is significantly inhibited, thus possessing a strong resistance to parasitic reactions. Mechanical characterization further reveals the superior tensile and adhesion strength of PAPTMA. Leveraging these properties, symmetric batteries employing PAPTMA hydrogel deliver exceeding 6000 h of reversible cycling at 1 mA cm−2 and maintain stable operation for 1000 h with a discharge of depth of 71%. When applied in 4 × 4 cm2 pouch cells with MnO2 as the cathode material, the device demonstrates remarkable operational stability and mechanical robustness through 150 cycles. This work presents an eclectic strategy for designing advanced hydrogels that combine high ionic conductivity, enhanced Zn2+ mobility, and strong resistance to parasitic reactions, paving the way for long-lasting flexible ZIBs. Highlights: 1 A novel cationic hydrogel electrolyte is prepared to address a significant challenge of balancing the tripartite trade-offs of hydrogel properties. 2 Cationic express pathways enable fast and selective Zn2+ transport through dynamic ionic repulsion, achieving high ionic conductivity (28.7 mS cm−1) and Zn2+ transference number (0.79). 3 The hydrogel demonstrates exceptional cycling stability across − 15 to 60 °C, showcasing great potential for practical flexible battery applications.